2018
DOI: 10.1021/acs.inorgchem.8b00226
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Cation Effects on Redox-Active Formazanate Ligands in Iron Chemistry

Abstract: Noncovalent interactions of organic moieties with Lewis acidic alkali cations can greatly affect structure and reactivity. Herein, we describe the effects of interactions with alkali-metal cations within a series of reduced iron complexes bearing a redox-active formazanate ligand, in terms of structures, magnetism, spectroscopy, and reaction rates. In the absence of a crown ether to sequester the alkali cation, dimeric complexes are isolated wherein the formazanate has rearranged to form a five-membered metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 91 publications
(73 reference statements)
1
29
0
Order By: Relevance
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…This is in stark contrast with compound 1, which fully converted to 1·THF in the presence of just asingle equivalent of THF. [10] AvantHoff analysis ( Figure S4) of 2 in THF gave DH8 8 = À4.3 AE 0.2 kcal mol À1 and DS8 8 = À16.9 AE 0.6 cal mol À1 K À1 .T he negative reaction entropy is consistent with binding of two THF molecules to form two molecules of monomeric THF-containing complexes.T he magnetic moment in [D 8 ]THF at room temperature from the Evans method is 4.9 AE 0.2 m B per monomeric unit, which is consistent with amononuclear high-spin Fe 2+ (S = 2) complex.…”
mentioning
confidence: 72%
“…We recently reported that Fe[N(SiMe 3 ) 2 ] 2 [9] gives access to low-coordinate Fe formazanate complex 1 (Scheme 2), and that THF contamination of solvent or starting materials results in the formation of complex 1·THF. [10] Herein, we show that these complexes both react with CO 2 to selectively give trimethylsilylisocyanate (TMSNCO) and the corresponding siloxide complex, and explain the unusually strong influence of THF through kinetic studies and through the isolation of akey intermediate.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Another study from these authors examined the effect of the countercation on the structures and reactivity of a series of derivatives of 21. 31 It was shown that when the countercation is one of the alkali metals (Na + , K + , Rb + or Cs + ), the compounds are dimeric in the solid state (22a-d, Scheme 7). In these dimers, the formazanate ligands coordinate in the 'open' form to give five-membered metallacycles, in which the 'pendant' terminal N-atom bridges to another Fe center.…”
Section: Group 8 (Fe Ru Os)mentioning
confidence: 99%